Burmagomphus chaukulensis, a new species of dragonfly (Odonata: Anisoptera: Gomphidae) from the Western Ghats, Maharashtra, India - Joshi, Shantanu; Sawant, Dattaprasad; Ogale, Hemant; Kunte, Krushnamegh (Zootaxa, 2022)
We describe a new species of dragonfly, Burmagomphus chaukulensis sp. nov., based on four males and two females from Chaukul, Sindhudurg, Maharashtra located in the Western Ghats biodiversity hotspot of India. The newly described species is diagnosed from its congeners by a combination of following characters: the shape of male caudal appendages (prominent lateral spines on cerci) and the lateral thoracic markings (stripe on mesepisternum reduced and pointed anteriorly). Additionally, B. chaukulensis is unique in terms of the shape of hamuli, strongly angulated with spines at both sides. An updated identification key to Indian Burmagomphus spp. is also provided.